The Effect Of Brand Ambasador and Prices on The Purchase Decision Of Android Hand Phone Through Interest In Buying Consumers In Medan City - Indawati Lestari; Martin; Marihot Manullang; Ribka Sari Butar-Butar; Zulia Rifda Daulay (Publisher Cv. Inara, 2021)
The main purpose of this study is to determine the effect of brand ambassadors and prices on purchasing decisions for Android phones through consumer buying interest. The approach in this study is associative with the data analysis used is path analysis. The population and sample in this study were 147 respondents who were selected by accidental sampling. The results showed that (1) brand ambassadors had a positive and significant effect on buying interest, (2) price had a negative effect on buying interest, (3) brand ambassadors had a positive and significant effect on purchasing decisions, (4) price had a negative effect on purchasing decisions, (5) brand ambassador has a positive and significant effect on purchasing decisions through buying interest, (6) price has a negative effect on purchasing decisions through buying interest.